2017
DOI: 10.1016/j.tetlet.2016.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Emission pathway switching by solvent polarity: Facile synthesis of benzofuran-bipyridine derivatives and turn-on fluorescence probe for zinc ions

Abstract: Bipyridine attached benzofuran derivatives were prepared by the cyclization of alkyne orthosubstituted phenols. Electronically different substituents, N,N-dibutylamino vs tert-butyl group, were attached on benzofuran rings. Depending on the polarity and pH of solvent environment, N,N-dialkylamino group participates in two distinctively different roles in emissive properties, i.e., ICT-type and PET-type behaviors. Upon capturing lone-pair electrons of N,N-dialkylamino groups by protonation, ratiometric blue-shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The actual development of practical probe molecules, however, often requires very thorough mechanistic understanding and complicated multistep synthesis to achieve the optimal properties. , Although there are several reported classroom examples where students can experience synthesis of fluorophores and dye molecules and can utilize them as probes, to the best of our knowledge, few of them have described a structure–reactivity relationship between probe molecule and target analyte. Herein, a laboratory class design for an advanced organic chemistry experiment is reported that readily visualizes (i) how mechanistic understanding can facilitate rational probe design and (ii) how subtle chemical modification can offer significant effects on chemical reactivity…”
Section: Introductionmentioning
confidence: 99%
“…The actual development of practical probe molecules, however, often requires very thorough mechanistic understanding and complicated multistep synthesis to achieve the optimal properties. , Although there are several reported classroom examples where students can experience synthesis of fluorophores and dye molecules and can utilize them as probes, to the best of our knowledge, few of them have described a structure–reactivity relationship between probe molecule and target analyte. Herein, a laboratory class design for an advanced organic chemistry experiment is reported that readily visualizes (i) how mechanistic understanding can facilitate rational probe design and (ii) how subtle chemical modification can offer significant effects on chemical reactivity…”
Section: Introductionmentioning
confidence: 99%
“…41 Therefore, these compounds can bring unique spectral and color changes with a specific metal ion. [42][43][44][45] Additionally, these compounds are thermally and photochemically stable. 46 Furthermore, the imine moiety having π electrons in C N bond prefers metal ions, causing variations in the ICT, thereby resulting in color changes.…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic compounds such as pyrrole, furan, and thiophene could enhance intramolecular charge transfer (ICT) by binding to metal ions because they can behave as electron donors or acceptors . Therefore, these compounds can bring unique spectral and color changes with a specific metal ion . Additionally, these compounds are thermally and photochemically stable .…”
Section: Introductionmentioning
confidence: 99%
“…Although elemental analysis techniques such as inductively coupled plasma mass spectrometry (ICP-MS) or optical emission spectrometry (ICP-OES) are well-established platforms that provide high accuracy and sensitivity to elemental impurities, the limited accessibility at point-of-use such as pilot plants or drug discovery space, cost, and limited high-throughput capability due to sample preparations are major drawbacks of ICP methods. , Therefore, there has been a need for alternative methods which are more user-friendly, portable, inexpensive, and high-throughput amenable, making them more suitable for on-line or at-line applications. One appealing approach is the fluorimetric and colorimetric method where a probe molecule responds to the target analyte with dramatic changes in emission and/or absorption. Those alternative approaches can provide a rapid and complementary tool to select appropriate treatment conditions for a residual metal removal process.…”
Section: Introductionmentioning
confidence: 99%